Systemy wczesnego ostrzegania w realizacji zasady kontynuacji działania - Kowalak, Robert (Early Warning Systems to Realize Going Concern Rule, 2007)
This article presents the usage of early warning systems in the realization of the rule of accountancy which is a going concern rule. The usage of statistical models is possible in early warning systems (singly and multidimensional) that are able to help auditors in giving away to the opinion what to the enumerated rule. These models have shown repeatedly that they are able to be a completion of the classic ratio analysis when making report referring to the estimation of financial condition of companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 107-114